Energy and environment : solid state simulation of novel photovoltaic and catalytic materials - Kehoe, Aoife B. (Trinity College (Dublin, Ireland). School of Chemistry, 2016)
The current global dependence on fossil fuels as the world’s primary energy supply presents many disadvantages, including the limited nature of these resources, the harmful effects their combustion has on human health and the environment, and the localisation of oil, in particular, in geopolitically unstable regions of the world. Of all the alternative sustainable power generation technologies, none possesses more energetic potential than solar energy. In this thesis, we first examine the materials used in thin film solar cells, using post-density functionaltheory simulation methods to examine the geometric and electronic structure of a range of novel materials. Firstly, three series of ternary copper based chalcogenides are examined with respect to determining their potential utility as cost effective and environmentally sound solarcell absorbers. Byanalysing key properties pertinent to photovoltaic application, such as band structure, effective mass, and optical absorbance, we ascertain if these systems could herald a generation of low cost, non-toxic, and widely available solarcell materials as a viable solution to the global energy crisis.
Keywords: Chemistry, Ph.D.; PhD Trinity College Dublin, 2016